MODEL KONSEPTUAL PERSEPSI MANAJEMEN TERHADAP KOMUNIKASI AUDITOR INTERNAL PADA TAHAP PEMANTAUAN TINDAK LANJUT - Widyaningsih, Hastuti; Mulyaningsih, Titiek (PRIMA EKONOMIKA, 2021)
This study aims to observe: 1) Whether the perception of the audit expectation gap from management affects the follow-up monitoring of internal audit. 2) Does formal and informal communication moderate the effect of perceptions on the audit expectation gap from management on monitoring of internal audit follow-up. 3) Does the use of technology moderate the effect of perceptions on the audit expectation gap from management on monitoring the follow-up of internal audit. There are three premises discussed in this study. Keywords: Audit Expectation Gap, Follow-up Monitoring, Internal Audit